Strengthening Village Administrative Governance in Realizing Excellent Service Through the Kradinan Archives Digitalization System "SIKENAN": Penguatan Tata Kelola Administrasi Desa Dalam Mewujudkan Excellent Service Melalui Sistem Digitalisasi Arsip Kradinan “SIKENAN” - Lestari, Yuni; Isbandono, Prasetyo; Weni Rosdiana; Dian Arlupi Utami; Cindy Pramita Agustin; Aditya Pratiwi Fitrianingrum (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The advancement of technology has shifted archival practices from conventional to digital methods. The digitization of archives is necessary to facilitate efficient and smooth archiving activities. Currently, the archiving process at Kradinan Village Office, Dolopo District, Madiun Regency, remains traditional, relying on manual record-keeping through tables in ledgers. This manual system often results in important files being overlooked, and retrieving old documents is time-consuming due to the physical format. Furthermore, paper documents are prone to damage, making long-term storage inefficient. This study aims to assist the Kradinan Village Office by digitizing their archive data to simplify archiving tasks. The application was developed using Microsoft Access, chosen for its capabilities in data input and document search functions. The research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as the methodological framework. The needs assessment involved observation and interviews to gather content requirements. For hardware and software necessities, Microsoft Access and a Windows 10 laptop were utilized. The resulting archive management system, named SIKENAN, was designed to be user-friendly and tailored to the specific needs of the village office, with additional features anticipated as necessary. The application was implemented at the Kradinan Village Office and followed by evaluation to refine and optimize the system.